The cherished five in Sikh history - Fenech, Louis (Oxford University Press, 2021)
1. Introduction: The Cherished Five, Guru Gobind Singh, and the Khalsa -- 2. The Number and Names of the Much-Loved Five -- 3. The Previous Lives of The Precious Five -- 4. The Five Beloved in Mid to Late Eighteenth-Century Gur-bilās Literature -- 5. The Five Adored in Early Nineteenth-Century Sikh Literature -- 6. The Treasured Five Move into The Later Nineteenth Century -- 7. The Panj Piare and Place: Twentieth-Century Ruminations -- Afterward -- Glossary -- Bibliography -- Appendix -- Prologue.